Experimental study on mercury removal from coal-fired flue gas by sulfur modified biomass coke with mechanochemical method. (1st February 2022) - Zhao, Shilin; Luo, Hui; Ma, Anjun; Sun, Zhiqiang; Zheng, Rongzhang
Graphical abstract: Highlights: Mechanochemical sulfur modified biomass coke was firstly prepared. Hg 0 removal follows BC-4-S2 Cl2 -MC > BC-CaHS-MC > BC-ES-MC > BC-NaHS-MC > BC-Na2 S-MC > R-BC. BC-S2 Cl2 -MC with 800 μL S2 Cl2 has the best Hg 0 removal rate of 96.17%. Sulfoxide benefits for mercury removal among all the sulfur forms. Mercury forms in the used MC-organic sulfur-BC are HgS with good stability. Abstract: Coal-fired power plants are the main anthropogenic source of mercury emissions in the atmosphere. In this work, the raw material of biomass (wood chips), modifiers of sulfur-containing substances (Na2 S, NaHS, S, CaHS, S2 Cl2 ), and mechanochemical method were adopted to prepare the mechanochemical sulfur-modified biomass coke (BC-S-MC). The effects of sulfur addition types and sulfur addition amounts on mercury removal performance of BC-S-MC were investigated by the mercury removal experimental device. The modification mechanism and mercury removal mechanism was explored with the help of BET, XPS, FTIR, and Hg-TPD. The results show that the mercury removal efficiency of BC-S-MC under the same sulfur addition amount meets BC-4-S2 Cl2 -MC > BC-CaHS-MC > BC-ES-MC > BC-NaHS-MC > BC-Na2 S-MC > R-BC. As S2 Cl2 addition amount increases, the mercury removal rate of BC-S2 Cl2 -MC firstly increases and then decreases with best value of 96.17%. Mechanochemical sulfur modification severely destroys the pore structure of R-BC, but affects the surface chemistry properties like sulfur forms, C = O, C = S, O–H, etc. Sulfoxide plays an important role in improving the mercury removal ability. The mercury forms in the used mechanochemical organic sulfur modified biomass coke are mainly HgS (black) and HgS (red), which have good stability.